2015
DOI: 10.2217/pgs.15.44
|View full text |Cite
|
Sign up to set email alerts
|

RNA Expression of Genes Involved in Cytarabine Metabolism and Transport Predicts Cytarabine Response in Acute Myeloid Leukemia

Abstract: This study highlights the importance of evaluating expression of candidate Ara-C metabolizing genes in predicting ex vivo drug response as well as treatment outcome. RI could be a predictor of ex vivo Ara-C response irrespective of cytogenetic and molecular risk groups and a potential biomarker for AML treatment outcome and toxicity. Original submitted 22 December 2014; Revision submitted 9 April 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…phosphorylation) of Ara-C. These results would be in agreement with other studies [19] showing an in vitro correlation between hENT1 and DCK expression and nucleoside analogs sensitivity in pediatric and adult AML [18]. Recently, a collaborative EORTC-GIMEMA trial has demonstrated a better response rate and survival with high dose Ara-C in very high risk setting patients, including AML FLT3-ITD cases [22], that presumably would show high hENT1 expression according to our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…phosphorylation) of Ara-C. These results would be in agreement with other studies [19] showing an in vitro correlation between hENT1 and DCK expression and nucleoside analogs sensitivity in pediatric and adult AML [18]. Recently, a collaborative EORTC-GIMEMA trial has demonstrated a better response rate and survival with high dose Ara-C in very high risk setting patients, including AML FLT3-ITD cases [22], that presumably would show high hENT1 expression according to our results.…”
Section: Discussionsupporting
confidence: 93%
“…Low levels of DCK tend to correlate with Ara-C resistance in childhood ALL and AML and adult AML [18, 30, 31]. Our observations suggest that DCK would not be a limiting step in Ara-CTP formation in patients with high FLT3 expression and thus, would support intracellular activation (i.e.…”
Section: Discussionmentioning
confidence: 85%
“…As our screen only identified DCK as a candidate Ara-C resistance gene and defective DCK is already a known mechanism of Ara-C resistance489, we decided to remove the ability of the CRISPR library to knock out DCK . To avoid DCK gene modification by the CRISPR library, the 5 DCK gRNA targeted sites were modified in a cDNA of DCK by introducing silent mutations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the uptake of cytarabine in leukemic blasts is highly sensitive to NBMPR, it has been assumed and asserted for several decades that cytarabine enters cells through an ENT1-dependent mechanism (1). This conclusion is supported by some (10, 11) but not all statistical association studies (1214), indicating that increased ENT1 mRNA abundance is correlated with increased cellular sensitivity or clinical responsiveness to cytarabine. More importantly, however, published studies to date employing heterologous expression systems have shown that cytarabine is either very weakly transported by ENT1 (<2-fold vs control) (15, 16) or is not transported by ENT1 at all (17).…”
Section: Introductionmentioning
confidence: 87%